Pre-operative fatigue in cancer patients: prevalence and associated factors - Oliveira, Murielly Marques de (2018)
This study aimed to describe the prevalence of fatigue and to identify factors associated withfatigue in patients in the pre-operative phase for oncologic surgery. We conducted a cross-sectionalstudywith 117 pre-operative cancer patients (mean age = 51.2 years; 76.9% women; 65.8% lived with a partner; 70.9% did not have previous cancer treatment). We used the instruments Piper Fatigue Scale-Revised; Perceived Stress Scale; Hospital Anxiety and Depression Scale; Pain Numerical Scale; Numerical Sleep Scale and Karnofsky Performance Status Scale. We conducted Chi-Square test, Student’s t-test, and one-way ANOVA. We found a 25.6% prevalenceof pre-operative fatigue and the intensity was moderate/severe. The affectivefatigue dimension presented higher score compared to behavioral and sensorial/psychological dimensions. Anxiety, depression, stress, pain, sleep and performance statuswere associatedwithpre-operative fatigue.